2019
DOI: 10.1161/circep.119.007174
|View full text |Cite
|
Sign up to set email alerts
|

Late Gadolinium Enhancement Magnetic Resonance Imaging Guided Treatment of Post–Atrial Fibrillation Ablation Recurrent Arrhythmia

Abstract: Background: Macroreentrant atrial tachycardia (AT) accounts for 40% to 60% of recurrent atrial arrhythmias after atrial fibrillation (AF) ablation. To describe late gadolinium enhancement magnetic resonance imaging (LGE-MRI)–detected scar-based dechanneling as new ablation strategy to treat ATs after AF ablation. Methods: Data from 102 patients who underwent initial AF ablation and repeat ablation for recurrent atrial arrhythmia within 1-year follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 32 publications
0
28
0
4
Order By: Relevance
“…In contrast to invasive EAVM during the ablation procedure, LGE-CMR-guided fibrosis management has improved our understanding of the individual underlying arrhythmia substrate during the natural course of human AF. Fochler et al (158) reported that an LGE-MRI anatomically guided approach for the treatment of recurrent arrhythmias post-AF ablation is feasible and effective. Similarly, another study highlights the potential use of the optimal set of patient-specific targets to ablate fibrotic atrial substrates (159).…”
Section: Treatment Approaches Targeting Atrial Fibrosismentioning
confidence: 99%
“…In contrast to invasive EAVM during the ablation procedure, LGE-CMR-guided fibrosis management has improved our understanding of the individual underlying arrhythmia substrate during the natural course of human AF. Fochler et al (158) reported that an LGE-MRI anatomically guided approach for the treatment of recurrent arrhythmias post-AF ablation is feasible and effective. Similarly, another study highlights the potential use of the optimal set of patient-specific targets to ablate fibrotic atrial substrates (159).…”
Section: Treatment Approaches Targeting Atrial Fibrosismentioning
confidence: 99%
“…This finding is consistent with the findings of the Delayed-Enhancement MRI Determinant of Successful Radiofrequency Catheter Ablation of Atrial Fibrillation (DECAAF) study, in which atrial fibrosis, as estimated by delayed enhancement on MR images, was found to be independently associated with the likelihood of recurrent arrhythmia [ 6 ]. MR LGE to identify the atrial substrate is important in two aspects: one is that it can avoid unnecessary AF ablation procedures, and the other is that it can be feasible and effective for targeting re-entrant drivers or anatomic MRI LGE detected gaps in the AF ablation strategy [ 23 , 24 ]. Therefore, our results indicate that atrial fibrosis, as estimated using MR LGE, may offer a robust means of determining optimal AF management and deciding upon preemptive strategies to prevent AF progression.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with recurrent AF were treated with a fibrosis homogenization approach, whilst, in those with recurrent atrial tachycardia, ‘dechanneling’ of LGE-CMR detected isthmi was studied. 80 In this later group, approximately half of patients were treated with ablation guided by established electrophysiological techniques whereas the remainder were treated dependent upon the LGE-CMR findings. Notably, the subsequent treatment response was similar (64–67% freedom from arrhythmia) across the three groups of patients thus studied (recurrent AF treated with LGE-CMR homogenization, recurrent atrial tachycardia treated with conventional approach and recurrent atrial tachycardia treated with LGE-CMR-guided dechanneling).…”
Section: Section 3: Using Advanced Imaging Techniques To Guide Ablation Proceduresmentioning
confidence: 99%